Fintech As Financial Inclusion: Factors Affecting Behavioral Intention To Accept Mobile E-Wallet During Covid-19 Outbreak - et. al., Shaliza Alwi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Mobile e-wallet or digital e-wallet is one of the emerging Financial Technologies (FinTech) that has become extremely prevalent during the last few years. As even the technology is growing, it is crucial that researchers recognize the factors that affect technology adaptation. Even, with the world's pandemic and the digitalisation of the banking system and modes of payment, it may have and disability. This research paper will therefore concentrate on defining the factors affecting behavioral intent to implement mobile e-wallet after the COVD-19 outbreak. The indicators highlighted in the paper are perceived usefulness , perceived ease of use, perceived health, perceived social impact, perceived value. Health alert, transactional costs and their impact on mobile e-wall adoption. The data was analyzed using multiple regression analysis, Alpha and Factor analysis from Cronbach. The study revealed a significant impact including its estimated model on the behaviour intent to implement mobile e-wallet.